Toward a better understanding on the role of unsteadiness in swimming propulsion - by means of PIV - Matsuuchi, K. (Biomechanics and Medicine in Swimming XI - Supplement, 2011)
The highly efficient locomotion of birds, insects and fish is based on unsteady dynamics. The central mechanism in the locomotion is related to unsteady behaviour of vortices such as the formation in boundary layers and the shedding from it. Attention to the relation between an object and vortex movement was first noticed in the aeronautical field. The problem of a thin airfoil performing small lateral oscillations in a uniform stream of incompressible fluid, received interest for many years, at the heart of all flutter prediction. Much research within the limitation of the linear perturbation theory was published in early times. Well-documented summaries, including Wagner`s work (1925) can be seen in Bisplinghoff (1955). While much tention was given to the lift sustaining insect and bird flights against their weight, relatively little interest has been given to the unsteady mechanism in swimming propulsion. In Colwin`s book (2002), we can find many detailed sketches of vortices generated during various stroke patterns. Even with the use of this sophisticated means, it is difficult to measure a whole flow field directly around human hand and foot. However, a great success was attained in the field of insect and fish locomotion. Recently the way approaching the unsteadiness by solving numerically the Navier-Stokes equations has been developing, actively but the reliability is somewhat poor and there are many cases in which the experimental validation is needed. The only tool for analysing unsteady flow is particle image velocimetry (shortly PIV). Matsuuchi et al. (2009) explained the principle of PIV and presented the application to swimmers. In this paper, we introduce several flow fields generated either by a hand motion while executing crawl stroke or by mono-fins as well as during the sculling motion of hand are visualized. Velocity and vorticity fields are especially important to understand the unsteady force generation as well as the question how unsteady flow is generated by the motion of hand and foot. Comparative report is also given about simultaneous measurements of unsteady force acting on a robot hand-arm system in motion and the properties of unsteady flow field obtained by PIV. In addition, the results by numerical simulations based on the vortex element method are presented within the 2D cases.